Kepercayaan Diri dan Penyesuaian Sosial dengan Employability pada Siswa SMK - Fandi Rosi Sarwo Edi (Happiness: Journal of Psychology and Islamic Science, 2021)
This study aims to determine the relationship between self-confidence and social adjustment with employability in vocational students. The research population was 184 class XI students, with a sample of 109 students using purposive sampling technique. Collecting data through the self-confidence scale proposed by Lauster (2012), the social adjustment scale proposed by Hurlock (1978), and the employability scale proposed by Super (2006). Data analysis used multiple regression and correlation techniques. The results of the research on the regression test obtained Fcount 121.74 with a significance of 0.000, it can be concluded that there is a very significant positive relationship between self-confidence and social adjustment and student employability.